Organization of accounting for fixed assets depreciation - Yaroslav Sheverya; Kateryna Hanusych; Шеверя Ярослав (II. RFKMF, 2024)
Abstract. A significant mechanism for allocating the cost of fixed assets to expenses and the cost of production is depreciation. The amount of accrued depreciation will impact financial results, the residual value of non-current assets in the balance sheet, and other important indicators of financial reporting. The organization of fixed asset accounting should ensure a complete and objective reflection of the actual physical and moral wear and tear of fixed assets. The question of depreciation and its reflection in accounting has been explored in the works of Petruk, O. M., Khvist, V. V. [1,2], Popova V.D., Kizima N.M. [3], Garasym P. M. [4], Kontseva V., Boyko N., Masalitina V. [5], Veriga Yu. A., Novokhatka N. O. [6], Yatsko M.V., Yatsko L.B [7]. Depreciation is the systematic allocation of the cost of fixed assets over various periods during their use. This entails the gradual expensing of the cost of fixed assets over the duration of their operational life.
Організація бухгалтерського обліку амортизації основних засобів
A tárgyi eszközértékcsökkenés számvitelének megszervezése
Keywords: accounting; fixed asset